2010
DOI: 10.1111/j.1475-5890.2010.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Tax and the Crisis*

Abstract: Did taxation play any role in precipitating the financial crisis? Are there lessons to be drawn for future tax reform priorities? This paper reviews the main channels by which tax effects might have been felt and which may require forceful attention. These include in particular the large tax biases favouring debt finance and, in some countries, investment in housing. The complexities of national tax codes, and the international interaction between them, have, moreover, encouraged the use of complicated financi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 48 publications
0
44
0
3
Order By: Relevance
“…Besides the considerable financial losses, the fact that there is an even stronger lack of political interest in these issues, lack of investigative knowledge and lack of proper legislation in regard to dealing with these issues of the white informal economy can present a motivational factor for perpetration of these acts that are financially very rewarding for the perpetrators. The debate we wish to encourage is somewhat similar to that started by Keen et al (2010) or Palan et al (2010) on the role of taxes in crisis. Keen et al (2010) writes that tax distortions have had an impact on the financial crisis as taxes were a strong background factor influencing the behaviour of financial institutions and actors.…”
Section: Economic Crisismentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the considerable financial losses, the fact that there is an even stronger lack of political interest in these issues, lack of investigative knowledge and lack of proper legislation in regard to dealing with these issues of the white informal economy can present a motivational factor for perpetration of these acts that are financially very rewarding for the perpetrators. The debate we wish to encourage is somewhat similar to that started by Keen et al (2010) or Palan et al (2010) on the role of taxes in crisis. Keen et al (2010) writes that tax distortions have had an impact on the financial crisis as taxes were a strong background factor influencing the behaviour of financial institutions and actors.…”
Section: Economic Crisismentioning
confidence: 99%
“…The debate we wish to encourage is somewhat similar to that started by Keen et al (2010) or Palan et al (2010) on the role of taxes in crisis. Keen et al (2010) writes that tax distortions have had an impact on the financial crisis as taxes were a strong background factor influencing the behaviour of financial institutions and actors. The similar discussion by Palan et al (2010) also showed that tax havens and offshore funds (and experts employed there) have significantly helped in the whole questionable securitisation process as their flexibility has speeded up legislation or actually enabled the processes.…”
Section: Economic Crisismentioning
confidence: 99%
“…In general, the price sensitivity of demand for housing is inversely related to the extent of preferential tax treatment for housing and to the expected rate of house price appreciation. Moreover, [4] note that mortgage interest tax relief encourages the build-up of gross housing debt and there is evidence that countries offering more favorable tax treatment for home ownership do indeed have higher ratios of mortgage debt. There is also evidence that mortgages fell significantly relative to home value (in UK and U.S.) after reforms reduced the value of mortgage interest relief (e.g.…”
Section: Tax Reliefs For Housingmentioning
confidence: 99%
“…Andrews et al (2011) warn that preferential fiscal treatment of credit-financed housing investment can be reflected in heightened house prices. Keen et al (2010) propose that taxation-induced bias in favor of credit-financed housing investment can put financial stability at risk. Hilber & Turner (2014) emphasize that the tax deductability of mortgage interest payments is capitalized into house prices rather than home ownership attainment, in particular in an environment where housing supply is inflexible.…”
Section: Housing-related Fiscal Policy and Societal Outcomesmentioning
confidence: 99%